(untitled) (Malaysian Journal of Civil Engineering, 2018)
Seismic response of a base isolated building is studied for varying properties of Lead rubber bearing. An eight storied educational building is taken into consideration as a structure of interest. Properties of the lead rubber bearing are altered to find the most optimum value of important parameters to obtain a minimum earthquake response of the building. The most important parameters are taken into consideration: initial stiffness (K1), yield strength (Fy/W) and post-to-pre yield stiffness (K2/K1). Three different ground motions are considered in the present analysis and applied in the longitudinal direction of the structure. Base shear, roof acceleration and bearing displacement are utilized to evaluate the performance of the isolated building. It is found that these parameters influence the response of the building significantly and seismic response of the structure reaches to a minimum value for a specific value of the bearing parameter. Finally, some recommendations are made based on the present seismic analysis with different ground motions.